EVALUATION OF HANDLING OF CHILDREN WITH SPECIAL NEEDS IN PRIMARY SCHOOL INCLUSION - Ratu, Kurniayu T.R.A (JPI (Jurnal Pendidikan Inklusi))
According to article 15 of Law No. 20 of 2003 on National Education System, that kind of education for children with special needs is Special Education. Article 32 (1) of Law No. 20 of 2003 imposes limits that Special Education is education for students who have difficulty in following the learning process because of physical, emotional, mental, social, and/or have the potential intelligence and special talents. The purpose of this study was to determine the treatment of children with special needs in inclusive schools in elementary school inclusion and know the resistance received by teachers in dealing with children with special needs in elementary school inclusion Glagah subdistrict in Lamongan district. Researchers used purposive sampling to choice of subjects in this study, to specialize in the subject in accordance with the purpose or goal of this study. Subjects in this study were three teachers who teach in the classroom who are children with special needs, the three principals in three schools as well as the inclusion of six parents whose children including children with special needs in inclusive schools in the District Glagah Lamongan. Technique data collecting by observation, interview techniques, and documentation techniques. The benefits of research to contribute about appropriate handler for special needs children who enroll in primary school inclusion. This study used a qualitative approach. This study was a qualitative descriptive.